PENGARUH MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR MATA KULIAH GEOMETRI RUANG PADA MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA - Lely Suryani; Yasinta Yenita Dhiki (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2020)
This study aims to determine the effect of learning media on student learning outcomes in mathematics education study programs. The method chosen in this study was a survey with a quantitative approach, and 40 students were randomly selected for the spatial geometry subject in the mathematics education program of the University of Flores. The Likert scale is used in the data collection technique instrument. Quantitative analysis was used with descriptive statistics, and involved Bivariate Correlation (Pearson), Classical Assumption Test, and hypothesis testing. The results showed that the learning media (X1) was seen as having a positive effect on learning outcomes (Y), this can be seen through the correlation analysis for R recruitment for X1 to Y of 0.529 and the significance value between X1 to Y two asterisks (**) so that there are positive influence with a significance level of 1%. In other words, the more or better the learning media, the student learning outcomes will increase and the better.